First Seminar on agriculture and food (conclusions) - Allpanchis, Revista (1979)
Under the auspices of the Friedrich Ebert Foundation and the SINEA Project National Development Foundation, the Academic Program of Social Sciences of the Pontifical Catholic University of Peru organized the First Seminar on Agriculture and Food. For three days (from October 10 to 13), more than one hundred specialists chosen for their knowledge and/or practical experience in the subject, from public organizations, universities, research centers and international institutions, working concentrated in Chaclacayo for 10 hours each day , listened to fifteen presentations, discussed and commented on them.